PRIORITY DIRECTIONS OF IMPROVING THE EFFICIENCY OF INVESTMENT AND INNOVATION ACTIVITIES OF ENTERPRISES - Кукина, Н. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
In market conditions; the management of innovation activity depends on a large extent on the effectiveness of the enterprise using the capabilities of the market environment and a clear system of planning the company’s resources; primarily financial; in the implementation of innovative projects; which in turn requires an analysis of the possibilities for obtaining financing; conditions and methods of its implementation. The formation and modernization of the domestic economy are considered to be the basis for the growth of the welfare of society; the consolidation of independence and the role of the state in the international arena. The innovative development of the economy takes into account the increase of the competitiveness of the companies; their adaptation to new business conditions; and the increase of the pace of production renewal. Ensuring a high level of scientific and technical development of the country; improving the results of innovation activities of enterprises require creating conditions for structural changes in the economy; increasing of the volume of innovation financing; state regulation and support of innovative processes; the use of effective forms of managing of the new developments; increasing competitiveness and the quality of the products of domestic producers. In this regard; there is a growing need for effective management of innovation; selection and implementation of company development strategies. The importance of innovation is growing rapidly all over the world. Dynamics and quality of financial recovery in the modern world are increasingly guided by the degree of science formation; innovations and the effective implementation of information and marketing strategies in enterprises. The innovative way are becoming recognized as the world’s leading financial systems. Innovation has become the dominant idea that unites the world economy.